Integration of physical and spiritual recreation of youth in the socio-educational animation - N.A. Maksimovskaya (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose - to reveal the possibilities of physical and spiritual recreation by combining them in the process of socio-educational animation. It examines the conceptual apparatus, which is the basis of development of methodology for the study of the recreational potential of the animation. Investigated the social and educational value of the integration of physical and spiritual recreation during the implementation of the animation activity among young people. The paper summarizes the current trends of social and pedagogical aspects of physical recreation. We consider the interpretation of the essence of the animation, which is to enhance the personality of its involvement in activities account recreational and educational opportunities animation. Defended the idea that the physical recovery - the basis of social optimism and social creativity. Settles integrated approach to social and educational animations to enhance the physical and social activity of the young man, the prevention of social passivity. Provides advanced methods and forms of recreation during the implementation of the animation business. It is proposed to use intensively games, theatrical performances, tourist travel, sports event.